SPAAR in action - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
SPAAR (the Washington-based Special Program for African Agricultural Research) is collaborating with regional organizations m the development of regional frameworks for action in agricultural research for four regions of sub-Saharan Africa: - the...